PERCEPTION OF LOCAL PEOPLE TOWARDS THE PROSTITUTIONS AND ITS IMPACTS IN DISTRICT HYDERABAD, SINDH PROVINCE OF PAKISTAN - Sajjad Ali Mallah; Abdul Rasool; Farhan Akhtar; Darya Khan Sanjrani (Scholar Express Journal, 2021)
Prostitution is the business or practice of providing sexual services to another person in return for payment. Prostitution profession is emerging rapidly worldwide, particular in Pakistan. The purpose of this study is to investigate the perception of local people towards prostitution and its impacts over the societies of Sindh, province of Pakistan. This study is qualitative in nature and based on in-depth interviews with the 10 respondents from different areas of Hyderabad. On behalf of the data collection from local people, the results revealed that, the prostitution is being considered to be as one of the worst act of the society, which is generally done for the sack of money or drug addiction. In findings, there were multiple pushing factors of women/children/male involvement into sex work, like, unemployment, poverty, sex for enjoyment, trafficking and drug addictions. In view of the results, the prostitution have some sort of negative impacts over the society as well as high incidence of violence to other girls/children’s too who are far from those evil works. Besides that, the prostitutes were of the opinion that the prostitution is an act made for the issues in family, diseases as well as poverty which force the local people to fall in such evils. With regards to the recommendations, this study may not generously contribute in generating recommendations but some of the suggestions could be useful for government as well as political institutes. It is suggested that government should ensure the implementation of law with regards to the prostitution. However, the rights should be provided to those who are doing this kind of work for the sack of different aspects as to eradicate such evil from the society as a whole
Keywords: Perception; Impacts; Prostitutions; Sindh